Novel mannose binding natterin-like protein in the skin mucus of Atlantic cod (Gadus morhua) - Rajan, Binoy; Patel, Deepti Manjari; Kitani, Yoichiro; Kiron, Viswanath; Brinchmann, Monica Fengsrud (Fish & Shellfish Immunology, 2017)
Author's accepted version (post-print). Available from 23/07/2018. acceptedVersion